Combination of vitamin d and e in supporting glutathione peroxidase and superoxide dismutase roles in insulin resistant neuronal cells - Siti Ruhana Ramli. (2017)
Introduction: Oxidative stress is an imbalance of free radicals' formation and antioxidant levels. Glutathione peroxidase (GPx) and superoxide dismutase (SOD) are antioxidant enzymes that play roles in protecting the body against oxidative stress. GPx and SOD are amongst the antioxidant enzymes that are mostly abundant in human cells. SOD plays its role in reducing superoxide (O₂⁻) to non-radical ROS hydrogen peroxide (H₂0₂). GPx is then reduced an inactivate H₂0₂ to water. Overabundance of oxidants and low concentration or absence of these antioxidant enzymes lead to oxidative stress that strongly affiliated to insulin resistance. Insulin resistance is one of the causes that lead to degeneration of the neuronal cells. consequently leading to neurodegenerative disease such as Alzheimer's disease (AD). Vitamin E has been shown to possess potent antioxidant, anti-inflammatory, anticancer. and neuroprotection. Vitamin D plays role as antioxidant, increase the insulin sensitivity, thus, increasing the glucose uptake. Objective: To elucidate the effect of the combination treatment of vitamin D and E in substituting roles of GPx and SOD in suppressing oxidative stress in insulin resistant neuronal cell cultures. Methodology: Neuronal cells (SK-N-SH) were cultured and optimized in MEM growth medium. Cells were induced with insulin resistance or hyperinsulinemia for 16 hours. Treatment with vitamin D, vitamin E, and combination of vitamin D and E were given for 24 hours. No treatment was given for negative control. RNA was extracted and converted into cDNA. Gradient PCR was performed for insulin receptor (INSR), glucose transporter 4 (GLUT4), glutathione peroxidase 1(GPx1) and superoxide dismutase 2 (SOD2) primer prior to real time PCR. Lastly, gene expressions of GPxl and SOD2 genes were carried out by using real time PCR. All the data obtained was reported as the mean ± SEM. One way ANOVA was used as a statistical analysis with Tukey test as Post Hoc Analysis for comparison of each treatment with control using SPSS (version 17.0) where p-value less than 0.005 considered as significant. Results: The results showed the gene expression of INSR and GLUT4 in negative control were down regulated upon high concentration of insulin. Vitamin D was significantly increased the expression of INSR and GLUT4. Combination of vitamin D and E showed the most significant effect in expression of GPx1 and SOD2. Conclusion: Vitamin D significantly up regulates the expression of INSR and GLUT4 in insulin resistant neuronal cells. Besides, combination of vitamin D and E significantly up regulates the expression of GPx1 and SOD2.